Penanaman Hidroponik dan Olahannya Sebagai Pencegahan Berat Badan Kurang di Desa Cibitung Wetan, Pamijahan, Bogor - Heny Agustin; Indri Indrawan (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2021)
Trilogi University with the community ‘Kampung Ramah Lingkungan’ (KRL) Seroja Kahuripan have conducted underweight prevention services in Cibitung Wetan Village, Pamijahan, Bogor. This service activity aims to educate importance of nutritious food, train in creating greenhouses and hydroponic installations, cultivate vegetable crops and their processing to increase the food value as prevention of underweight. The method was carried out in several stages: 1) The preparation and coordination; 2) Implementation; and 3) monitoring and evaluation. Based on the data, it was known that 13,69% of children aged 0–23 months are observed with underweight with body weight far below the standard and 34,44% of children are approaching as underweight. Efforts to prevent underweight were carried out by strengthening the identity of partners, the construction of greenhouse and hydroponic installation as well as training in vegetable cultivation carried out by the team so that partners can be independent in providing nutritious food. The yields of vegetables and their processed products in form of nuggets and jerky have provided food value added increasement to partners. As a result, increasement in the number of partner members from 15 to 54 people, the formation of a group logo as identity reinforcement, the construction of greenhouse facilities and hydroponic installations series, increasement of partner’s knowledges and skills in hydroponic cultivation and crops processing, and increasement partner’s awareness of underweight issue. The results of partner’s satisfaction questionnaire showed that 85% were very satisfied with the program and they hoped for sustainable and further fostering.